David J. Hildner, Poetry and truth in the Spanish works of fray Luis de León. Tamesis, London, 1992; 177 pp. - Altenburg, Nancy (El Colegio de México, 1994)
Se reseñó el libro: Poetry and truth in the Spanish works of fray Luis de León.